Anesthetic Management of Traumatic Rupture of Aorta and Diaphragm at Shahid Gangalal National Heart Centre - Upreti, Murari Raj; Pokharel, Jeju Nath (Nepalese Heart Journal, 2017)
Traumatic transaction thoracic aorta and rupture diaphragm carries high mortality rate. It needs specialized centre which is able to handle such case and prompt intervention. Even with maximum effort, only 5 to 7% of the victim will survive and get discharged from the hospital.